The Impact of Television Programmes on Teenage Career Aspirations: The 'MasterChef Effect' - Giorgio Di Pietro (Institute for the Study of Labor (IZA), 2016)
In recent years, in Italy, a larger number of students have chosen to attend vocational hospitality and catering schools. This paper investigates the extent to which this increase may have been triggered by the growing popularity of the cooking reality show MasterChef, in which the chef profession is portrayed as exciting and glamorous. Using panel data methods and controlling for several potential confounding variables, the analysis attempts to separate the effect of MasterChef from that of other determinants of the decision to attend vocational hospitality and catering schools. The results show that an increase of one percentage point in the audience of MasterChef is associated with an increase in the proportion of final year lower secondary school students willing to enrol at vocational hospitality and catering schools of between 0.25 and 0.35 percentage points. This finding suggests that popular television programmes like MasterChef may play an important role in complementing and supplementing government measures aimed at promoting vocational training among youths.
Keywords: I21; J44; C23; 330; teenage career aspirations; vocational hospitality and catering schools; panel data analysis; MasterChef